RELEASE OF SILICON FROM SILICATE MATERIALS AND ITS UPTAKE BY RICE PLANT - Linca Anggria; Husnain Husnain; Kuniaki Sato; Tsugiyuki Masunaga (Indonesian Agency for Agricultural Research and Development, 2017)
Plants absorb silicon (Si) from soil solution in the form of monosilicic acid, also called orthosilicic acid (H4SiO4). Application of organic and inorganic materials containing readily soluble Si can increase Si supply in the soil and its uptake by plant. The study aimed to evaluate the release of Si from organic and inorganic material sources and its uptake by rice plant. The released phosphorus (P) from those materials was also evaluated. The inorganic materials evaluated included fly ash, steel slag, silica gel and Japanese silica gel (JSG), while the organic materials consisted of rice husk ash (RHA), rice husk burnt (RHB), media of mushroom (MM), cacao shell biochar (cacao SB) and rice straw compost (RSC). The dynamics of Si and P were observed by periodical samplings at 7, 17, 24 and 34 days after transplanting (DAT). Tiller number and plant height were measured at 16, 21 and 36 DAT. The results showed that Si concentration in solution derived from inorganic material was highest for JSG followed by silica gel (1.107 and 0.806 mmol L-1, respectively). The release of Si from organic material was higher for RHB and RHA (0.618 and 0.539 mmol L-1, respectively). Cacao SB, silica gel, JSG and RHB significantly increased plant height at 36 DAT. Meanwhile, Si materials did not significantly affect the tiller number. Of the materials used, steel slag and JSG significantly affected Si uptake by rice plant.